CP-167 Suitability of the "beliefs about medicines" questionnaire for HIV patients on combined antiretroviral treatment. (24th March 2015) - Capoulas, M; França, L; Castro, S; Santos, P; Ching, F; Lobo, T; Ferreira, D; Marques, E; Fernandez-Llimos, F; Santos, C
Abstract : Background: Non-adherence to combined anti-retroviral treatment (cART) is one of the key factors leading to treatment failure, higher morbidity, mortality, and health costs. Tools to evaluate adherence are beneficial since they allow health care workers to focus on patients with adherence problems. "Beliefs about Medicines Questionnaire" (BMQ) is a tool that evaluates the patient's awareness of the "need" for and "concerns" about their medicines. Purpose: To evaluate whether the findings of the BMQ questionnaire correlated with adherence in HIV patients. Material and methods: BMQ was applied to HIV-infected patients on cART with three or more pharmacy visits who gave informed consent. Adherence was evaluated through refill date records. Results: Of a total of 175 patients, 80 (45.7%) were women, 97 (55.4%) were previously treatment-naïve, and the median age was 44 years old. Average BMQ-specific "need" and "concerns" scores were 22.6 [Standard Deviation (SD) = 2.7] and 18.6 [SD = 5.0], respectively. The average difference between "need" and "concerns" scores (N-C) was 4.0 [SD = 6.1]. Average refill adherence was 101% [SD = 9.1%] with values between 59% and 129%. The majority of patients (86.3%) had refill adherence between 80% and 110%, and 2.3% had refill adherence below 80%. Although we observed a tendency for higher values of N-C in patients with higher refill adherence, it was not possible to establish a correlation due to lack of statistical significance. Conclusion: It wasn't possible to correlate the results of the BMQ-specific questionnaire with adherence, probably due to the fact that there was a high proportion of treatment-naïve patients. We observed higher refill adherence rates in treatment-naïve patients, which may be due to the fact that these patients are most likely to be aware of the "need" for cART. It's possible that the BMQ-specific questionnaire is more useful in treatment – experienced patients in order to identify causes of non-adherence. References and/or Acknowledgements: No conflict of interest.